1990
DOI: 10.1093/jxb/41.10.1293
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and Light Activation of Ribulose 1,5-bisphosphate Carboxylase in the Presence of Starch

Abstract: Limitation of photosynthesis and light activation of ribulose, 1,5-6/.sphosphate carboxylase (RuBPCO) were examined in the 5th leaf of seedlings of red clover (Trifolium pratense L. cv. Renova) for 5 d following an increase in photosynthetic photon flux density (PPFD) from 200 to 550fttnol quanta m" 2 s" l . Net photosynthesis and its stimulation at 20 kPa O 2 , initial activity of rapidly extracted RuBPCO, standard activity of RuBPCO after incubation of the extracts in the presence of CO 2 , Mg 2 + , and inor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

1992
1992
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 13 publications
1
17
1
Order By: Relevance
“…However the mechanism is not understood, and there are discrepancies between the various investigations, e.g. whereas Rubisco activation increased in our studies and in red clover (Grub and Mfichler 1990), it declined in soybean but could be reactivated in vitro by incubation with Pi (Sawada et al 1990). Further studies are needed to resolve these discrepancies, and to relate them to known mechanisms for regulating Rubisco.…”
Section: Discussioncontrasting
confidence: 56%
“…However the mechanism is not understood, and there are discrepancies between the various investigations, e.g. whereas Rubisco activation increased in our studies and in red clover (Grub and Mfichler 1990), it declined in soybean but could be reactivated in vitro by incubation with Pi (Sawada et al 1990). Further studies are needed to resolve these discrepancies, and to relate them to known mechanisms for regulating Rubisco.…”
Section: Discussioncontrasting
confidence: 56%
“…They suggested that the activity of carbamylated Rubisco sites was being reduced by an unknown mechanism in response to carbohydrate accumulation induced by cold girdling. Grub and Machler (1990) also reported a reduction in the catalytic effectiveness of activated Rubisco while carbohydrates were accumulating following transfer of low-light-grown red clover to a higher light intensity. The similarity between our present observations and those of Krapp and Stitt (1995) and Grub and Machler (1990) encourages speculation that there might be a common underlying mechanism.…”
Section: Possible Causes For Slower Turnover Of Carbamylated Rubisco mentioning
confidence: 92%
“…Grub and Machler (1990) also reported a reduction in the catalytic effectiveness of activated Rubisco while carbohydrates were accumulating following transfer of low-light-grown red clover to a higher light intensity. The similarity between our present observations and those of Krapp and Stitt (1995) and Grub and Machler (1990) encourages speculation that there might be a common underlying mechanism. Perhaps in some unknown way, carbohydrate accumulation induces by another means the same reduction in the ability of activase to stimulate catalysis by carbamylated Rubisco that we observe as a result of reducing the content of activase itself.…”
Section: Possible Causes For Slower Turnover Of Carbamylated Rubisco mentioning
confidence: 92%
“…Seemann and Sharkey 1986;von Caemmerer and Edmondson 1986;Sharkey 1989;Sage et al 1990). However, exceptions have been reported (Seemann 1989;Grub and Machler 1990). Anyway, full activation and high RuBP would still be consistent with shared control if Rubisco were nevertheless not fully RuBP-saturated in vivo (see Woodrow and Berry 1988;Sharkey 1989 for a discussion of this problem), or if additional factors affect the in-vivo activity of Rubisco (see Woodrow and Mott 1988), or if control is exerted by factors which control the access of CO2 to the active site (see below).…”
Section: Contribution Of Rubisco To the Control Of Photosynthesismentioning
confidence: 99%